The Advantages of the Phonics Method for Early Childhood Reading Skills - Nur Audina; Siti Ma’muroh; Rima Novia Ulfa (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2022)
Teaching foreign languages especially reading for early chilhood is more challenging and applying an interesting method is needed to improve their ability. Teachers must have known some of easy and fun methods for early chilhood so that the learning process can run well. One method that can be used is the phonics method. Phonics is a method for teaching reading and writing of the English language by developing the letters of the alphabet and their sounds first for their phonemic awareness and an understanding of the links between these sounds and how to use the letters of the alphabet to represent them. A child learning phonics will see a